Contamination Associated With Glove Changing Techniques in the Operating Theatre - Boekel, Pamela; Ek, Eugene T. (Frontiers in Surgery, 2022)
Background: Sterility of the operative field during surgery is imperative in reducing the risk of infection. Most commonly, double gloves are worn by surgeons and when contamination occurs, the top gloves are changed intra-operatively. No studies have investigated which technique is best. We aim to identify which top glove changing technique causes the least surface contamination. Methods: Glitterbug™ (UV fluorescent powder) was applied to the top gloves of 3 individuals who changed their top gloves according to a randomized method – Method 1: 3 pairs worn, remove the outer pair; Method 2: 2 pairs worn, remove the top glove, replace unassisted; and Method 3: 2 pairs worn, remove the top glove, and replace assisted by a scrub nurse. A blinded investigator inspected for Glitterbug™ contamination under UV light. Results: 210 trials were performed. Two types of contamination were identified: direct contact and airborne spread. For absolute contamination: Method 1 had 59/64 (92%) contaminated trials, Method 2 had 49/65 (75%) contaminated trials, and Method 3 had 64/81 (79%) contaminated trials. This was statistically significant (p=0.031). For direct contamination only: Method 1 had 38/64 (59%) contaminated trials, Method 2 had 24/65 (37%) contaminated trials and Method 3 had 20/81 (25%) contaminated trials. This was statistically significant (p<0.0001). Conclusions: Method 2 had a statistically significant lower contamination rate overall, with Method 3 having the lowest direct contamination rate. We believe that wearing 2 gloves, removing the top glove and replacing it, either assisted or unassisted, could decrease surface contamination of the sterile field.